So little time. 5, Tell me about it - Stine, Megan (New York : HarperEntertainment, 2002)
Get invited to the party of the century. Sneak out of the house after curfew. Cover for your friend when her parents ask questions. Don't get caught!
"A Parachute Press Book"--T.p.
"Based on the hit TV series"--Cover.
Based on the teleplay by Michael Baser and Frank Dungan.
Includes bibliographical references (p.) and index.
All Ages.
Keywords: Parties -- Juvenile fiction; Series